Societal Legacy of Communism in the Post-Soviet Era: From Collective Thinking to State-Oriented Thinking - Gogashvili, Manana (European Scientific Journal, ESJ, 2026)
This paper examines the enduring societal legacy of communism in the post-Soviet era, arguing that the collective mindset cultivated under Soviet rule has not enabled a full transition to state-oriented civic thinking. Rather than embracing pluralism and civic independence, many post-Soviet societies continue to imagine themselves as homogeneous entities in which unity is frequently equated with conformity. The study explores the ideological, psychological, and cultural foundations of post-Soviet political behavior and political culture in transitional societies. It aims to illuminate the persistent challenges faced by post-Soviet states in overcoming their communist inheritance and developing civic-minded, participatory societies capable of sustaining civil governance. Methodologically, this article is an analytical review that combines philosophical interpretation, documentary comparative analysis, and critical engagement with relevant scholarly literature. The analysis demonstrates that the apparent emergence of individualism often conceals continued ideological submission and political passivity. Without a broader philosophical and civic transformation—extending beyond institutional and structural reform—post-Soviet societies remain caught between the promises of freedom and the comfort of conformity. This research contributes to political sociology, transitional studies, and post-communist scholarship by clarifying the persistence of collective mentalities and social conditioning shaped during the Soviet period.